1979
DOI: 10.1002/eji.1830090612
|View full text |Cite
|
Sign up to set email alerts
|

T cell tolerance in the chicken. II. Lack of evidence for suppressor cells in tolerant agammaglobulinemic and normal chickens

Abstract: Tolerance to human y-globulin (HGG) at the T cell level was readily induced in both normal and bursectomized FP and E L 6 strain chickens by intravenous injection of 5 to 50 mg of soluble HGG. T cells from tolerant chickens, subsequently immunized with HGG in complete Freund's adjuvant (CFA), failed to cooperate in the adoptive immune response to 2,4,6-trinitrophenylated (TNP) HGG with TNP-immune spleen cells. However, suppressive activity could not be demonstrated when cells from tolerant chickens were combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1979
1979
1988
1988

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Although the role of SSA is unclear, it is conceivable that SSA may play a role in the perpetuation of the disease. This would be reminiscent of findings in bursectomized birds, where transplantabie suppressor T-cells were consistently detected (Blaese et al 1974, Grebenau & Thorbecke 1978. Together with the recent finding in similar patients of normal numbers of pre-B-cells expressing cytoplasmatic immunoglobulin (Vogler et al 1976, Pearl et al 1978, our data suggested that B-lymphocytes in these patients may be inherently able to complete at least some early steps in differentiation such as those required for IgM antibody responses.…”
Section: Immunodeficiency and Excessive Suppressor Activity •supporting
confidence: 88%
See 1 more Smart Citation
“…Although the role of SSA is unclear, it is conceivable that SSA may play a role in the perpetuation of the disease. This would be reminiscent of findings in bursectomized birds, where transplantabie suppressor T-cells were consistently detected (Blaese et al 1974, Grebenau & Thorbecke 1978. Together with the recent finding in similar patients of normal numbers of pre-B-cells expressing cytoplasmatic immunoglobulin (Vogler et al 1976, Pearl et al 1978, our data suggested that B-lymphocytes in these patients may be inherently able to complete at least some early steps in differentiation such as those required for IgM antibody responses.…”
Section: Immunodeficiency and Excessive Suppressor Activity •supporting
confidence: 88%
“…Some characteristics of this PFC response are summarized in Table XIL In striking contrast to normals, patient PFC precursor cells did not bear slg determinants. This would be reminiscent of findings in bursectomized birds, where transplantabie suppressor T-cells were consistently detected (Blaese et al 1974, Grebenau & Thorbecke 1978. Another surprising difference was the observation that the addition of the T-cell mitogen PWM resulted in suppression of patient, but not the normal PFC response.…”
Section: Immunodeficiency and Excessive Suppressor Activity •mentioning
confidence: 72%
“…33). Another explanation might be that suppressor T cells fail to proliferate in the absence of certain B cells or of B cell products ( 16). This alternative would particularly apply for anti-idiotype suppressor T cells.…”
Section: Discussionmentioning
confidence: 99%